EVALUATION OF THE CONSUMPTION OF OXYGEN (VO2MÁX.) IN TEST OF BANK: A LONGITUDINAL STUDY IN STUDENTS OF THE PREPARATORY NUCLEUS OF OFFICIALS OF THE RESERVATION (NPOR) FULL IN THE 16TH REGIMENT OF AUTOMATED CAVALRY (RECMEC) (Fiep Bulletin - online, 2014)
The aim of this study is to measure the VO2max in ascent and descent bench test in three moments, during the officials' of the reservation preparatory course. Methodology: it's an applied research, longitudinal, analytical, and probabilistic. The sample consisted of 15 active men, average of age 18,07±0,5 years old. The stature was measured (m), body mass (kg), heart frequency of effort (HFE) it was controlled the phases, increment of the height of the bench (cm), number of touches per minute (t/m) ascent and descent rhythm of the ergometric bench and time of execution. The individuals used a cardiofrequencimeter of the Polar mark A5 in the gauging of CF and the Table of Borg in the subjective control of the effort. The ergometric test applied was the Test of electronic bench of Cirilo (TEBC) in three different moments (3 months of interval): AVL 01, AVL 02 and AVL 03 of the year 2005. The used statistics was descriptive of average, deviation-pattern, maximum and minimum and inferential through the test of Friedman for repeated measures. The significance level was p
Keywords: Ergometrics; Step Test; Military; Aptitude cardiorespiratory